Functional and molecular glycobiology - Brooks, Susan A; Dwek, M. V; Schumacher, Udo (Bios Scientific Publishers, 2002)
Functional and Molecular Glycobiology provides a comprehensive basis to the study of carbohydrates and their roles in the life sciences. The book explains the chemistry of carbohydrates, and the biosynthesis and diversity of different types of glycans. It looks at the functional role of glycoconjugate compounds in normal cellular processes, in both disease and development The book also describes how these compounds can be studied, analysed and manipulated for use in biotechnology. Functional and Molecular Glycobiology is a unique introduction to the field and it bridges the gap between introductory books and current research. The book is in the BIOS series Advanced Texts.
Advanced text
Keywords: glykosfingolipidy; biologie; Glycoconjugates; biochemie; glykoproteiny; glykokonjugáty; Glycoproteins; Glycosphingolipids